Stimulation of the basal and central amygdala in the mustached bat triggers echolocation and agonistic vocalizations within multimodal output - Ma, Jie; Kanwal, Jagmeet S. (Frontiers in Physiology, 2014)
The neural substrate for the perception of vocalization is relatively well described, but we know much less about how the timing and specificity of vocalizations is tightly coupled with audiovocal communication behavior. In many vocal species, well-timed vocalizations accompany fear, vigilance and aggression. These emotive responses likely originate within the amygdala and other limbic structures, but the organization of motor outputs for triggering species-appropriate behaviors remains unclear. We performed electrical microstimulation at 461 highly restricted loci within the basal and central amygdala in awake mustached bats. At a subset of these sites, high frequency stimulation with weak constant current pulses presented at near-threshold levels triggered vocalization of either echolocation pulses or social calls. At the vast majority of locations, microstimulation produced a constellation of changes in autonomic and somatomotor outputs. These changes included widespread co-activation of significant tachycardia and hyperventilation and/or rhythmic ear pinna movements. In a few locations, responses were constrained to vocalization and/or pinna movements despite increases in the intensity of stimulation. The probability of eliciting echolocation pulses versus social calls decreased in a medial-posterior to anterolateral direction within the centrobasal amygdala. Microinjections of kainic acid at stimulation sites confirmed the contribution of cellular activity rather than fibers-of-passage in the control of multimodal outputs. The results suggest that multimodal clusters of neurons may simultaneously modulate the activity of multiple central pattern generators present within the brainstem.